RETRACTED: Asfour et al. Amitriptyline-Based Biodegradable PEG-PLGA Self-Assembled Nanoparticles Accelerate Cutaneous Wound Healing in Diabetic Rats. Pharmaceutics 2022, 14, 1792 - Hani Z. Asfour; Nabil A. Alhakamy; Osama A. A. Ahmed; Usama A. Fahmy; Mohamed A. El-moselhy; Waleed Y. Rizg; Adel F. Alghaith; Basma G. Eid; Ashraf B. Abdel-Naim (Pharmaceutics, 2024)
Pharmaceutics retracted the article “Amitriptyline-Based Biodegradable PEG-PLGA Self-Assembled Nanoparticles Accelerate Cutaneous Wound Healing in Diabetic Rats” [...]